Watching Battlestar Galactica in Australia and the Tyranny of Digital Distance - Leaver, Tama (Australian Film Television & Radio School, 2008)
In an era where communication technologies can move digital media at close to the speed of light, this paper explores the rupture between this technical potential and the actual model by which international television screening dates are determined in Australia. As the delays between overseas and Australian airdates can be as long two years, and average over six months, the rapid rise in both official and fan-produced online material and interaction relating to television series has given rise to a massive but largely unfulfilled demand for simulataneous access to episodes across the globe. Using the case study of the critically acclaimed fan favourite Battlestar Galactica, this paper outlines some of the strategies by which producers build global fan loyalty - from official websites, blogs, commentary podcasts and online deleted scenes to exclusive webisodes and official participation in fan forums. The paper argues that these trends, combined with the time delay between release dates, are the largest factors contributing to the unlawful downloading of television via peer-to-peer file-sharing platforms such as BitTorrent. In attempting to maintain distribution models that began as geographic necessitites, but have become exclusively political and economic decisions in an era of digital communication technologies, this paper argues that media corporations are perpetuating a 'tyranny of digital distance' and alienating their own audiences.